COMBINATION OF TEMPEH AND CARROT PREVENT ATHEROSCLEROSIS WISTAR RAT: Indicated by Increase of HDL and Total Antioxidant, Decrease LDL, F2-Isoprostan, and IL-6 - Ari-Agung, I G. A.; Suryadhi, N. T.; Mantik, N. A.; Suter, I K.; Partama, and I. B. G. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
Coronary heart disease (CHD) is the leading cause of death, either in developed and developing countries. The disease is stimulated by the present of atherosclerosis. This study aims to investigate supplementation of combined tempeh M-2 and carrot to prevent atherosclerosis wistar rat by increases HDL and TAC, decreases LDL, F2-Isoprostan, and IL-6.  This was a true experimental study with the factorial completely randomized post-test only control group design.  variables such as KN (standard feeding / pellets (50 g / kg bw / day), KP: pig lubrication: pellets (1: 9) (50 g / kg bw / day), T : lubrication pig: pellets (1: 9) with tempeh M -2 (20 g / kg bw / day), W: pig lubrication: pellets (1: 9) with carrots (20 g / kg bw / day), and TW: pig lubrication: pellets (1: 9) with tempeh M-2 (20 g / kg bw / day), and carrots (20 g / kg bw / day).  Dependent variables in this study are serum HDL,serum TAC, LDL serum, urine F2-Isoprostan, and plasma IL-6 (with Elisa Method). Data were analyzed using the F test (two-way ANOVA), followed by LSD test. Descriptive research was also conducted in this study in order to find out the change of aortic histopathologic. The highest average levels of HDL, TAC contained on TW, which respectively amounted 68.640 ± 0.50 mg / dl, 1.454 ± 0.01 nM / mL. It showed highly significant differences (p<0.01) in the various treatments.  TW treatment showed highly significant interaction effect (p<0.01) were observed for all parameters except for HDL. Average levels of LDL, F2- Isoprostan, and IL-6  lowest in the treatment TW, which respectively amounted  20.718 ± 1.33 mg / dl, 0.720 ± 0.065 ng / dl, 35.328 ± 1.000 pg/dl, showed highly significant differences (p<0.01) in the various treatments. It can be concluded that supplementation with a combination of tempeh M-2 with carrots give the best effect, can increases HDL and TAC, and can decreases LDL, F2-Isoprostan, IL-6 significantly, and may change the hystopathology  structure of aorta from endotel dysfunction to become normal.